Kernel methods in bioengineering, signal and image processing [electronic resource] - Camps-Valls, Gustavo , 1972-; Martâinez-Ramâon, Mane , 1968-; Rojo-Alvarez, Jose Luis , 1972- (Idea Group Pub, 2007)
"This book presents an extensive introduction to the field of kernel methods and real world applications. The book is organized in four parts: the first is an introductory chapter providing a framework of kernel methods; the others address Bioegineering